Self-actualization As The Factor Of Psychological Health Of women Who Raise Children With Special Needs - Huliaieva, Olena (Visnyk of V.N. Karazin Kharkiv National University. Series Psychology, 2016)
The article shows the results of empirical research of level and structure of self-actualization in mothers, raising children with special needs. The obtained data’s analysis points that the desire for self-actualization is common for them, they strive to develop themselves, and this is the sign of their psychological health. But eventually the self-actualization level of women, who raise disabled children, has a negative downward trend.